2023
DOI: 10.1177/00031348231153551
|View full text |Cite
|
Sign up to set email alerts
|

Examining Health Disparities in Orthopedic Care During COVID-19

Abstract: Background Demographics and socioeconomic status affect the delivery of medical care resulting in healthcare disparities. The purpose of this study was to investigate the impact of COVID-19 on existing healthcare disparities, including access to healthcare in the outpatient orthopedic surgery clinic. Methods The medical records of 3006 patients treated at the University of Kentucky Orthopedic Surgery Department prior to COVID-19 (April 2018, 2019), and during the COVID-19 pandemic (2020) were retrospectively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A national study on 767 hospitals assessing all payer types found that White patients experienced the greatest reduction in elective surgeries, compared to other racial groups, suggesting that the pandemic did not exacerbate racial disparities in elective surgical care [6] . Further studies in bariatric, cardiac, and orthopedic surgical subspecialties revealed that patient populations were more diverse (lessened racial and SES disparities) after the onset of the pandemic for some surgical procedures but less diverse (greater racial and SES disparities) for others [7] , [8] , [9] , [10] . Studies assessing academic general surgery departments, however, showed that male, White, and privately insured patients were more likely to undergo medically-necessary procedures during the pandemic [11] and that patients with higher SES (commercial or non-governmental insurance) were more likely to utilize both in-person and telemedicine visits during the pandemic [12] .…”
Section: Introductionmentioning
confidence: 99%
“…A national study on 767 hospitals assessing all payer types found that White patients experienced the greatest reduction in elective surgeries, compared to other racial groups, suggesting that the pandemic did not exacerbate racial disparities in elective surgical care [6] . Further studies in bariatric, cardiac, and orthopedic surgical subspecialties revealed that patient populations were more diverse (lessened racial and SES disparities) after the onset of the pandemic for some surgical procedures but less diverse (greater racial and SES disparities) for others [7] , [8] , [9] , [10] . Studies assessing academic general surgery departments, however, showed that male, White, and privately insured patients were more likely to undergo medically-necessary procedures during the pandemic [11] and that patients with higher SES (commercial or non-governmental insurance) were more likely to utilize both in-person and telemedicine visits during the pandemic [12] .…”
Section: Introductionmentioning
confidence: 99%